2017
DOI: 10.1525/elementa.147
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of cattail (Typha spp.) management techniques depends on exogenous nitrogen inputs

Abstract: Wetlands occupy a position in the landscape that makes them vulnerable to the effects of current land use and the legacies of past land use. Many wetlands in agricultural regions like the North American Midwest are strongly affected by elevated nutrient inputs as well as high rates of invasion by the hybrid cattail Typha × glauca. These two stressors also exacerbate each other: increased nutrients increase invasion success, and invasions increase nutrient retention and nutrient loads in the wetland. This inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…The elevated N concentrations and greater biomass production of T. × glauca also result in greater ecosystem N retention (Currie et al 2014). Yet, when invasive Typha is treated with herbicide to meet management objectives, decreased plant demand results in increased soil inorganic nutrient availability (Lawrence et al 2016b;Elgersma et al 2017), which may set the stage for reinvasion, algal blooms, or export of nutrients to adjacent aquatic systems. Nutrient release is of particular concern in ecosystems such as the Everglades, where downstream ecosystems are oligotrophic.…”
Section: Nutrientsmentioning
confidence: 99%
See 1 more Smart Citation
“…The elevated N concentrations and greater biomass production of T. × glauca also result in greater ecosystem N retention (Currie et al 2014). Yet, when invasive Typha is treated with herbicide to meet management objectives, decreased plant demand results in increased soil inorganic nutrient availability (Lawrence et al 2016b;Elgersma et al 2017), which may set the stage for reinvasion, algal blooms, or export of nutrients to adjacent aquatic systems. Nutrient release is of particular concern in ecosystems such as the Everglades, where downstream ecosystems are oligotrophic.…”
Section: Nutrientsmentioning
confidence: 99%
“…Typha response to nutrient enrichment is stronger than that of many competing species (Newman et al 1996;Woo and Zedler 2002), suggesting that Typha management could be more effective if combined with nutrient reductions (i.e., treating an underlying cause of Typha dominance). In a modeling study, Elgersma et al (2017) found that reducing nutrient inputs was more effective at limiting Typha growth compared to herbicide, fire, or mowing in the absence of nutrient reductions. A small-scale experimental study using C additions to sequester N demonstrated that reductions in nutrient availability can reduce the competitive ability of a nitrophilic wetland invader (Perry et al 2004), but largescale application of this approach is logistically challenging, especially in wetlands.…”
Section: Nutrient Managementmentioning
confidence: 99%
“…aboveground biomass is recommended in highly productive areas or in constructed wetlands, in order to avoid the accumulation of organic matter after decomposition (Álvarez and Bécares, 2006;Vroom et al, 2018). Elgersma et al (2017) results showed that in high-nutrient wetlands the most effective combination to manage cattail hybrid invasion was herbicide with burning, proposing that nutrient inputs in wetland ecosystems can improve management efforts. Johnson et al (2019) reported that one year after mechanical harvesting of dominant clonal cattail, the light transmission increased due to the aboveground biomass removal, while a submerged harvest lead to soil nutrients increasing availability.…”
Section: Resultsmentioning
confidence: 99%
“…This trend has been linked to increased sediment accumulation and subsequent water volume loss in playas (O'Connell et al, 2012); however, increased exotic species richness could also be linked to greater N runoff associated with cropped watersheds. Elgersma et al (2017) linked invasive emergent vegetation abundance, specifically Typha spp., to increased nutrient loading in wetlands globally. Further, different plant species may have variable N uptake capacities (von Wiren et al 1997).…”
Section: Discussionmentioning
confidence: 99%